Determinants of functional limitations in basic and instrumental daily activities among older adults living in rural settings: a cross-sectional study - Suyasa, I Gede Putu Darma; Agustini, Ni Luh Putu Inca Buntari; Sutini, Ni Kadek (Universitas Airlangga, 2026)
Introduction: Maintaining the functional capacity of older adults is essential to support independence, particularly in rural areas. Understanding the factors contributing to the reduced ability to perform activities of daily living (ADLs) and instrumental activities of daily living (IADLs) is essential for developing effective gerontological nursing strategies. This study identified the predictors of ADL and IADL impairment among older adults residing in rural communities. Methods: This cross-sectional study involved 318 older adults selected through simple random sampling. The Barthel Index and Lawton IADL Scale were used to measure ADL and IADL abilities. The Geriatric Depression Scale was used to assess depressive symptoms, whereas difficulties in vision, hearing, and communication were evaluated using the Washington Group Short Set. Chi-square tests and logistic regression were used to examine the associations and predictors. Results: ADL and IADL disabilities were identified in 4.4% and 10.1% of the respondents, respectively. Communication difficulties were a strong predictor of both ADL and IADL disabilities (AOR = 13.72; 95% CI = 3.26–57.76, p < 0.001 and AOR = 7.07; 95% CI = 2.34–21.34, p < 0.001). Depressive symptoms increased the risk of ADL disability (AOR = 4.17; 95% CI = 1.24–14.05, p = 0.021), and adults aged ≥ 75 years showed higher odds of IADL impairment (AOR = 4.39; 95% CI = 1.89–10.16, p < 0.001). Conclusions: Challenges in communication and depressive affect functional capacity among rural older adults. Maintaining independence and improving daily functioning by implementing early identification and intervention targeting communication and mental health are essential.